(3CbQGW GdPgH aj GdeaGNQI Hjf GdQhVI hHFQ GdYRHs - (3YHO Gddg Hf Ydj Hf CMeO Hf eMeO GdMSfj Gdjefj GdUfYGfj, GdeYQha HGdhRjQ,J (B1147 (3g` s ((3jhSa Hf CMeO Hf jhSa Hf GdMSf Hf GdMSf s)
(3ChdgG (B:s
(3GdMeO ddg GdPj CfTG LfGJ eYQhTGJ hZjQ eYQhTGJ, HMSH eTJgi YHGOg hGdfNd hGdRQY eNJdakG Ccdg s
(3BNQgG (B:s
(3hUd jGQH Ydi SGej GdOQL hBdg eG EHJgLJ Jdc GdaQL HeG Qhi HQbhb YfgG haQL hYLd Gddge efc HGdaQL hHGdbHhd cf dfG ebGHdkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3GdChQGb GdChdi hGdCNjQI ePgHIs
(3hgj ebGeI COHjI aj GdefGXQI Hjf GdQhVI hHFQ GdYRH hgeG ef VhGMj UfYGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B107 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B86s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B52 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs